Shout out! Podcasts as sources of non-degree further education, counter-publics and entertainment (Sociologisk Forskning, 2022)
This article is woven into the multi-disciplined research field concerned with questions on young people’s living conditions and cultural expression in stigmatized residential areas in Sweden’s metropolitan areas. In recent years, a movement demanding social justice has emerged in these areas. In this article, we examine the content of four podcasts that may be considered central to this social movement. The study has three specific purposes that relate to the contributions of this article. First, we examine how the podcasts, like the social movement in general, can be seen as an expression of how marginalized young people deal with their position as subordinated citizens and the racism that is part of their everyday living conditions. Second, our analysis shows how podcasts serve as meeting places for young people in the marginalized suburbs, as well as providing arenas for resistance in the form of counter-publics. Third, the study contributes to knowledge of the potential role of podcasts in contemporary non-degree further education. This is achieved through an analysis of the learning processes shown in the podcasts.
Keywords: non-degree further education; podcasts; counter-publics; stigmatized suburbs; youth